Pengaruh Pelatihan, Reward, dan Lingkungan Kerja terhadap Kinerja Karyawan Pada PT Metal Hitech Engineering - Firnanda, Novia; Baskoro, Heru (SAFE-Network, 2025)
This study aims to analyze the effect of training, rewards, and work environment on employee performance at PT Metal Hitech Engineering. In an era of ever-changing business, it is important for companies to improve the quality of human resources in order to compete effectively. The method used in this study is a quantitative approach with data collection through questionnaires distributed to employees. The sample taken was 64 respondents with a nonprobability sampling technique. The data analysis technique used was multiple linear regression analysis and partial hypothesis testing (t-test) using SPSS 25. The results of the study showed that the independent variable, namely training (X1) partially did not have a significant effect on employee performance (Y), while the Reward (X2) and Work Environment (X3) variables partially had a significant effect on employee performance (Y). The conclusion of this study confirms that to improve employee performance, companies need to optimize training programs, provide appropriate rewards, and create a conducive work environment. This study is expected to be a reference for companies in formulating strategies to improve employee performance and provide insight for further research that is relevant to this topic.